2015
DOI: 10.1016/j.exppara.2015.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Oral dependent-dose toxoplasmic infection model induced by oocysts in rats: Myenteric plexus and jejunal wall changes

Abstract: Toxoplasmosis is a widely distributed disease caused by the protozoan Toxoplasma gondii that is mainly transmitted orally. Once ingested, the parasite crosses the intestinal barrier to reach the blood and lymph systems to migrate to other regions of the host. The objective of this study was to evaluate the changes in the myenteric plexus and the jejunal wall of Wistar rats caused by oral infection with T. gondii oocysts (ME-49 strain). Inocula of 10, 100, 500 and 5000 oocysts were used. The total population of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 35 publications
2
8
0
Order By: Relevance
“…This increase may represent a protective mechanism, as nNOS is involved in maintaining the integrity of the mucosa (epithelial barrier) and epithelial secretion in the gastrointestinal tract . Our data are in accordance with other studies in the myenteric plexus of the jejunum of rats in the chronic phase of toxoplasmosis . This increase does not necessarily represent cell proliferation, but rather a change in phenotype …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This increase may represent a protective mechanism, as nNOS is involved in maintaining the integrity of the mucosa (epithelial barrier) and epithelial secretion in the gastrointestinal tract . Our data are in accordance with other studies in the myenteric plexus of the jejunum of rats in the chronic phase of toxoplasmosis . This increase does not necessarily represent cell proliferation, but rather a change in phenotype …”
Section: Discussionsupporting
confidence: 92%
“…Toxoplasma gondii oocysts of the ME‐49 strain, genotype II, were used. The animals of infected groups received 1.0 ml of oral suspension containing 5000 sporulated T. gondii oocysts . The CG received the same volume of sterile saline solution.…”
Section: Methodsmentioning
confidence: 99%
“…This phenomenon may indicate a relationship between the immune response against the parasite and the production of nitric oxide in the myenteric plexus. This is corroborated by similar studies of the jejunum of these animals (VICENTINO-VIEIRA et al, 2015) and that of pigs (ODORIZZI et al, 2010), in which a genotype III strain was used. However, no studies were found about the effects of toxoplasmosis infection on the NADPH-d + neurons specific to the colon.…”
Section: Discussionsupporting
confidence: 71%
“…This divergence in findings is explained by differences in the experimental protocol, such as the evolutionary form of the inoculated parasite and the genotype of the strain. A study of the small intestine in which a similar experimental protocol was used revealed neuronal loss with inoculum loads of 10, 100, 500 and 5000 oocysts, demonstrating a greater depletion effect of the infection on neurons in the initial part of the intestines (VICENTINO-VIEIRA et al, 2015). This can be explained by the natural presence of a larger number of intraepithelial lymphocytes in the small intestine, resulting in a more intense immune response with greater release of cytokines and other inflammatory mediators, and hence, greater tissue damage (BEAGLEY et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that the infection can compromise the intestinal structure and innervation, even in immunocompetent individuals with no classic clinical signs of toxoplasmosis . We observed local inflammation that was possibly induced by the presence of the parasite in the organ, reflected by the presence of tissue cysts and parasitic DNA . The submucosal plexus and EGCs appear to play a primordial role in the response to infection .…”
Section: Introductionmentioning
confidence: 77%